Fungal biomass potential: production and bioremediation mechanisms of heavy metals from municipal organic solid waste compost - Nuñez, W. E. (2023)
The compost produced based on municipal/urban organic solid waste (RSOM/U), is a valuable resource as a biofertilizer for agriculture, gardening, forestry and especially for soil remediation, whose production contributes to sustainable development through recycling of organic matter and nutrients. However, due to the raw materials used, the compost can have a significant content of heavy metals such as: cadmium (Cd), lead (Pb), arsenic (As), mercury (Hg) and selenium (Se), and contaminants such as potentially toxic trace elements that harm human health. These components can accumulate in plant tissues by absorption, giving rise to the possibility of being bioavailable to humans and animals. The fungal bioremediation of heavy metals in RSOM/U compost is highly efficient, cost-effective, available and friendly to the environment, therefore the removal of metals through this technique is a priority, if the purpose is to use it in agricultural soils. This review summarizes the studies based on the potential of fungal biomass for the bioremediation of heavy metals in RSOM/U compost, reporting information on RSOM/U-based compost, fungal biomass production and mechanisms of bioremediation of heavy metals by fungal biomass. In conclusion, the bioremediation of heavy metals using the fungal biomass in RSOM/U compost, with adequate segregation of raw material, coupled with bioremediation, could improve the removal of heavy metals in RSOM/U compost, and could be an ecological and viable alternative, which must be valued by intensifying its use.